EFFECTIVENESS OF TOMATO LEAF EXTRACT (SOLANUM LYCOPERSICUM) AGAINST THE GROWTH OF STAPHYLOCOCCUS AUREUS - Pradipta, Rafly; Budianto, Nugroho Eko Wirawan (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2026)
Staphylococcus aureus is a Gram-positive bacterium that commonly causes infections in humans. The increasing prevalence of antibiotic resistance necessitates the exploration of alternative natural antibacterial agents. Tomato (Solanum lycopersicum) leaves contain bioactive compounds such as alkaloids, flavonoids, and phenolics that may exhibit antimicrobial properties. This study aimed to determine the antibacterial effectiveness of tomato leaf extract against S. aureus. A true experimental design was conducted using the disk diffusion method. Tomato leaf extract was prepared in concentrations of 25%, 50%, and 75%. The treatments included a positive control (antibiotic) and a negative control (Aquadest). Inhibition zones were measured after incubation, and data were analyzed statistically to determine significance among groups. The tomato leaf extract demonstrated inhibitory activity against S. aureus at all tested concentrations. The 75% concentration exhibited the strongest inhibition with an average diameter of 20.86 mm (categorized as very strong), followed by 50% (7.86 mm, moderate) and 25% (6.47 mm, moderate). Statistical analysis showed significant differences among all treatment groups (p < 0.05). Tomato (Solanum lycopersicum) leaf extract effectively inhibits the growth of Staphylococcus aureus, with the highest antibacterial activity observed at a 75% concentration. These findings suggest the potential of tomato leaf extract as a promising natural alternative for antibacterial therapy, particularly against antibiotic-resistant strains.